Salmonella Typhi – a Quiet Bacteria with a Loud Message: an ICU Case Report - Adu-Gyamfi, Rossi; Hoosain, Fatima; Chetty, Sean (DiscoverSys Inc., 2019)
Typhoid fever, caused by Salmonella enterica, serovar Typhi, is restricted to humans as its host and evades the human immune system with ease. This quality has been one of the many reasons why it is commonly found as an endemic bacterium in emerging economies. Also, due to a remarkably low yield from blood cultures (median of 1 CFU/mL of blood), Salmonella septicemia is uncommon. New evidence gathered together with clinical investigations have provided insight into the mechanisms that underlie the pathogenesis of typhoid, host restriction as well as antibiotic and vaccine susceptibility. However, very little has been done to curb the persistence of disease and emergence of resistant strains. We discuss a case of Salmonella Septic Shock in the Intensive Care Unit (ICU) that takes us through various aspects in diagnosis, the treatment potential and the problems surrounding prevention.